8(x+5)=4(2x+3)+28

Simple and best practice solution for 8(x+5)=4(2x+3)+28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+5)=4(2x+3)+28 equation:


Simplifying
8(x + 5) = 4(2x + 3) + 28

Reorder the terms:
8(5 + x) = 4(2x + 3) + 28
(5 * 8 + x * 8) = 4(2x + 3) + 28
(40 + 8x) = 4(2x + 3) + 28

Reorder the terms:
40 + 8x = 4(3 + 2x) + 28
40 + 8x = (3 * 4 + 2x * 4) + 28
40 + 8x = (12 + 8x) + 28

Reorder the terms:
40 + 8x = 12 + 28 + 8x

Combine like terms: 12 + 28 = 40
40 + 8x = 40 + 8x

Add '-40' to each side of the equation.
40 + -40 + 8x = 40 + -40 + 8x

Combine like terms: 40 + -40 = 0
0 + 8x = 40 + -40 + 8x
8x = 40 + -40 + 8x

Combine like terms: 40 + -40 = 0
8x = 0 + 8x
8x = 8x

Add '-8x' to each side of the equation.
8x + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4x-17=(3x-2)*4 | | 3x-3=7x+12 | | 4x=3y | | 3x-3=7x-12 | | 9x+5-4x-3+x=146 | | 2-6t-9-2t= | | -6-(2-3p)= | | -8n-9+7n= | | -[2z-(11z+1)]=1+(8z+6) | | x*0.1=20 | | -2z+11z+1=8z+6 | | 0.55x+.05(8-x)=.10(64) | | 20*x=0.1 | | -3+8x+4+(-10x)= | | -8y+(-2y)= | | 0.20(12)+0.05x=0.10(12+x) | | 7m+(-9m)= | | 74-2x=2x+22 | | 2x-5=4x+13 | | 8+2p-5=6p+8-3p | | -3x+12x= | | 7a+10a= | | 13c^2-52= | | 3(4x-3)=51 | | 4p^2+164p+81= | | (t+3)(t-4)=5 | | 100x^2+1400x+4500=0 | | x-121=4(x-5) | | -3x^2-31x+22=0 | | 10x+3=6-2x+3 | | n*9+4=58 | | 9m^3-7m^4+8m^2= |

Equations solver categories